2021
DOI: 10.1016/j.worlddev.2021.105389
|View full text |Cite
|
Sign up to set email alerts
|

The redistributive effects of pandemics: Evidence on the Spanish flu

Abstract: This paper examines the impact of a pandemic in a developing economy. Measured by excess deaths relative to the historical trend, the 1918 influenza in Spain was one of the most intense in Western Europe. However, aggregate output and consumption were only mildly a↵ected. In this paper we assess the impact of the flu by exploiting within-country variation in "excess deaths" and we focus on the returns to factors of production. Our main result is that the e↵ect of flu-related "excess deaths" on real wages is la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Barro et al (2020) run a panel regression of 1918 Spanish flu deaths on GDP and consumption, finding that it reduced GDP and consumption by 6% and 8% respectively. Basco et al (2020) found a large, negative effect of flu-related deaths on wages, increasing poverty amongst urban workers. Correia et al (2020) find flu had a negative effect on employment and output.…”
Section: Literature Within the Economics Disciplinementioning
confidence: 99%
“…Barro et al (2020) run a panel regression of 1918 Spanish flu deaths on GDP and consumption, finding that it reduced GDP and consumption by 6% and 8% respectively. Basco et al (2020) found a large, negative effect of flu-related deaths on wages, increasing poverty amongst urban workers. Correia et al (2020) find flu had a negative effect on employment and output.…”
Section: Literature Within the Economics Disciplinementioning
confidence: 99%
“…Pandemic uncertainty could reduce investments in both physical and intangible capital (Lorentzen et al, 2008) and increase the volatility of stock markets (Bai et al, 2021), while the long-term effects on inflation and interest rates are less clear (Lee and McKibbin, 2004;Basco et al, 2021;Costa Junior et al, 2021). The higher health-care costs (Cuddington, 1993a,b), as well as the lower GDP (Acemoglu and Johnson, 2007), reduce savings and capital accumulation after pandemics, leading to decreased investments in capital and innovation (Chen et al, 2021).…”
Section: Mainstream Economic Approachmentioning
confidence: 99%
“…5 This is comparable with estimates of the immediate impact of COVID-19 (IMF April 2021; World Bank January 2021). However, studies disagree about whether the economic impact of the Spanish flu was short-lived (temporary) with a quick reversion to the trend or if it had long-run (permanent) impacts on well-being (Basco et al 2021). Additionally, there is an ongoing discussion about whether the Spanish flu pandemic tended to equalise societies (Jorda et al 2020) or if it led to an increase in within-country inequality (Basco et al 2021).…”
Section: What Can We Learn From Previous Health Crises?mentioning
confidence: 99%
“…However, studies disagree about whether the economic impact of the Spanish flu was short-lived (temporary) with a quick reversion to the trend or if it had long-run (permanent) impacts on well-being (Basco et al 2021). Additionally, there is an ongoing discussion about whether the Spanish flu pandemic tended to equalise societies (Jorda et al 2020) or if it led to an increase in within-country inequality (Basco et al 2021). These questions will also be important in the context of the COVID-19 pandemic, and they are related to identifying the pathways through which pandemics affect economic activity.…”
Section: What Can We Learn From Previous Health Crises?mentioning
confidence: 99%